IMPLEMENTACION DE UN SISTEMA CONTABLE EN UNA MICROEMPRESA DEL MUNICIPIO DE NACAJUCA, TABASCO. - Prats, Germán Martínez; Hernández Hernández, Sergio de los Santos; Magaña, Sergio Alfonso Tosca (IJRDO - Journal of Business Management, 2021)
Currently the business world is advancing rapidly and is in constant motion goes hand in hand with the changes that arise in technology, the new demands for information, the social, cultural and economic changes that exist in the environment. In this research we will talk about the accounting system and how it generates more information, strategic resources in organizations, which allows to improve the control of the company, manage decision making, so it is essential that all companies that provide services, design and thus implement it, in this Research Work develops the "Design of an accounting system for a Microenterprise", the accounting system is an important and essential tool, since they allow to analyze and evaluate the economic facts generated by the operations, providing information to the management for decision-making. The establishment of an accounting system in an entity is a complex process that if it is not well elaborated can negatively influence the results of business management, so nowadays the accounting system must be properly installed and operated by a qualified staff.